Investigate the efficiency of passive cooling cabinet on HPC systems - Tan, Wu Zong (Nanyang Technological University, 2023)
Data centres are critical for the expansion of cloud computing and are constantly being operated by organizations continuously. However, the excessive heat generated by servers can negatively impact the electronic components of computing devices, leading to increased energy consumption, and cooling demands. Traditional air-cooling methods are not efficient enough to promptly remove the extra heat, which has led to the need for designing data centres with higher cooling efficiency. This project aims to investigate the efficiency of passive cooling cabinets in data centres by comparing efficiency of passive cooling cabinet configurations. Using ANSYS FLUENT, the thermal distribution and airflow around server cabinets in a data centre are simulated. The results identify crucial problems such as overcooling and re-circulation of hot air. The simulation parameters were achieved from previous research of Sun HPC data centre and Investigation of Diverse Cold Air Inlet Configuration for Sun HPC Data Centre. The project. Further studies are recommended to include different server layouts simulation with more server and higher heat load to improve the reliability of the findings.